Terminal deletion of the long arm of chromosome 10. Issue 5 (October 1986) - Curtis, H; Howell, R T; Cope, C
Abstract : A de novo chromosome abnormality interpreted as a terminal deletion of chromosome 10, del(10)(pter----q25.2:), was ascertained in a newborn female with multiple malformations. The clinical features observed at birth and on follow up at 10 months of age are described and compared with previously reported cases.